Adverse Childhood Experiences and Trends of Deliberate Self-Harm in Indonesian Adolescents - Rawit, Devi Angelina Taminey; Tatipikalawan, Firens Victor; Christabela, Verina; Juniarta, Juniarta; Barus, Novita Susilawati (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2024)
Introduction: Deliberate self-harm (DSH) refers to a purposeful and intentional act of self-injury that individuals engage in as a means to regulate their emotions. This phenomenon is frequently observed throughout the period of adolescence, characterized by the onset of both physical and psychological transformations. There are multiple factors that contribute to the emergence of deliberate self-harm (DSH), with Adverse Childhood Experiences (ACEs) being one of them. Method: The primary objective of this study was to examine the correlation between adverse childhood experiences (ACEs) and the inclination towards deliberate self-harm (DSH) among adolescents in Indonesia. Results: The study employed a correlational quantitative methodology, and a accidental sampling was used to recruit 397 adolescent participants from Indonesia. The instruments employed in this study included the Indonesian version of the Adverse Childhood Experience Questionnaire (ACE.Q) with a Cronbach Alpha coefficient of 0.817, and the Deliberate Self-Harm Inventory (DSHI) with a Cronbach Alpha coefficient of 0.769. The data was analyzed to analysis using descriptive statistics and the Chi Square correlation test. The results of the study revealed a statistically significant association between Adverse Childhood Experiences (ACEs) and deliberate self-harm (DSH), with a p-value of 0.001. Conclusions: Further investigation aims to reveal additional variables that lead to the initiation of deliberate self-harm (DSH) and other adverse childhood experiences (ACE)-related problems. Parents, educational institutions, government entities, child protection organizations, and medical professionals are obligated to consistently comply with child safety legislation and guidelines.